COMPARISON OF CORE STABILIZATION EXERCISES AND PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION TRAINING ON PAIN RELATED NEUROMUSCULAR RESPONSE OUTCOMES FOR LOW BACK PAIN - Nimarta Fulwani; Mehwish Siddiqui; Aisha Ijlal; Muhammad Yasir Saeed; Khadija Irfan; Fatima Sehar; Jai Parkash; Muhammad Jazib; Attiq Ur Rehman (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Low back pain (LBP) is a highly prevalent musculoskeletal condition with a significant socioeconomic burden. Despite various treatment strategies, the most effective rehabilitation approach remains uncertain. Core stabilization exercises (CSE) and proprioceptive neuromuscular facilitation (PNF) training are commonly used physiotherapeutic interventions for managing LBP, yet direct comparisons of their effectiveness on pain-related neuromuscular outcomes are limited. Objectives: This study aimed to compare the effects of CSE and PNF training on pain related outcomes among low back pain patients. Methodology: An experimental study was conducted on 30 LBP patients (aged 18–50 years), divided into two groups receiving either a two-week CSE or PNF intervention. Pain intensity was measured using the Numeric Pain Rating Scale (NPRS), while functional disability was assessed with the Roland-Morris Disability Questionnaire (RMDQ). Pre- and post-intervention comparisons were made using paired t-tests. Data was analyzed by SPSS version 26. Result: Both groups showed significant improvements in all pain-related outcomes post-intervention (p < 0.05). However, the CSE group exhibited a greater reduction in pain intensity (72% vs. 65.2%) and a more significant improvement in functional disability scores compared to the PNF group. These findings suggest that CSE is superior in enhancing core stability and reducing pain. Conclusion: Two-week intervention showed that core stabilization exercises (CSE) is more effective in alleviating low back pain symptoms and improving neuromuscular function as compared to proprioceptive neuromuscular facilitation (PNF). Future research should explore long-term effects and optimal exercise protocols for sustained benefits.